KOLABORASI SEKOLAH DAN MASYARAKAT DALAM MENDUKUNG PENDIDIKAN - Reski Permata Sari; Nur Laila; Sitti Nurpaida; Idawati (STKIP Subang, 2025)
This article examines the relationship between schools and communities as a strategic component of primary school management. The study aims to analyze the concepts, principles, techniques, and forms of school–community relationships in supporting educational quality improvement. This study employs a qualitative descriptive approach through literature review of books, scientific journals, and educational policy documents relevant to school–community relations. The findings indicate that effective and sustainable collaboration between schools and communities contributes to improving learning quality, strengthening student character development, and enhancing school accountability. School–community relations function not only as communication activities but also as a managerial strategy to ensure community participation in planning, implementing, and evaluating educational programs. Therefore, strengthening school–community partnerships is essential for achieving sustainable and context-based primary education management.